Effect of freshness grade of anchovy (Engraulis encrasicolus) on the quality of marinated product stored at 4°C - Gokoglu, Nalan; Ucak, Ilknur (Universitas Malikussaleh, 2020)
The aim of this study was to investigate the effects of raw material freshness on the quality of marinated fish. The raw material anchovy (Engraulis encrasicolus) was divided into two batches. One batch (A) was kept at ambient temperature (20°C) for 6 h and the other one was kept at 0°C for 72 h. Then, they were marinated by soaking into marination solution containing 3% acetic acid and 8% NaCl. Total volatile basic nitrogen (TVB-N), trimethylamine (TMA), thiobarbituric acid (TBA), para-anisidine (p-Av) values in both marinated samples increased significantly during storage at 4°C. Increases in quality parameters were higher in samples produced with raw anchovy kept at 20°C compared to samples kept at 0°C. Although the sensory scores of both samples decreased during storage, higher scores were obtained for samples kept at 0°C compared to samples kept at ambient temperature. According to the results of the study, it has been determined that the quality of the raw material significantly (p<0.01) affects the quality of marinated anchovy.Keywords: fish; quality; anchovy; marinade; raw material